2014
DOI: 10.18187/pjsor.v10i3.770
|View full text |Cite
|
Sign up to set email alerts
|

Important TQM Implementation Contributors in Pakistani Petrochemical Sector

Abstract: This study discusses quality practices in Pakistani Petrochemical sector to understand TQM practices and their implementation in Pakistan. It helps to understand the role of leadership, vision & plan statement, employee participation and education & training as important constructs of TQM. It shows how these constructs help to speed up the TQM implementation in petrochemical sector like other constructs of TQM and finally company moves towards quality approach. The responses of executives, managerial staff and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
4
1
Order By: Relevance
“…Our results also correspond with the study by Adgaba [ 40 ], who reported a mean moisture content of 20.5 % in Ethiopian honey. However, our findings differ from Tewodros et al [ 41 ], who measured a moisture content of 16.0 ± 1.25 % in honey directly obtained from hives in Ethiopia, and from Latif et al [ 42 ], who found moisture content ranging from 14.3 to 18.6 % in Pakistani honey. A moisture content of more than 20 g/100g makes honey susceptible to fermentation and microbial spoilage [ 43 , 44 ].…”
Section: Resultscontrasting
confidence: 99%
“…Our results also correspond with the study by Adgaba [ 40 ], who reported a mean moisture content of 20.5 % in Ethiopian honey. However, our findings differ from Tewodros et al [ 41 ], who measured a moisture content of 16.0 ± 1.25 % in honey directly obtained from hives in Ethiopia, and from Latif et al [ 42 ], who found moisture content ranging from 14.3 to 18.6 % in Pakistani honey. A moisture content of more than 20 g/100g makes honey susceptible to fermentation and microbial spoilage [ 43 , 44 ].…”
Section: Resultscontrasting
confidence: 99%
“…Nevertheless, there are many factors influencing the SME export performance (Chen et al, 2016). The previous studies found an absence of total quality management (Haroon & Shariff, 2016;Latif et al, 2014;Saeed & Hasnu, 2011), market orientation (Asad et al, 2016;Hussain et al, 2016) in the manufacturing sector of Pakistan. Moreover, they indicated that owners of SMEs and Government of Pakistan should consider these factors for SME better performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are many factors influencing the SME export performance (Chen et al, 2016). The previous researchers found the absence of total quality management (Haroon & Shariff, 2016;Latif et al, 2014;Masakure et al, 2009;Saeed & Hasnu, 2011) in the manufacturing sector of Pakistan. Moreover, they suggested that owners of SMEs and Government of Pakistan should consider these factors for SME to increase the export performance.…”
Section: Literature Reviewmentioning
confidence: 99%